Empirical Analysis of the Effect of Foreign Direct Investment on Health Status in Sub-Saharan Africa: What Role for Governance? - Ayenagbo, kossi (Innovation Journal of Social Sciences and Economic Review, 2022)
This study aims to empirically investigate how governance affects the impact of foreign direct investment (FDI) on health outcomes in Sub-Saharan Africa, focusing on infant and child mortality rates. The study employs an econometric approach, using a dynamic panel model for 44 Sub-Saharan African countries over the period 2002 to 2019. The Generalized Method of Moments (GMM) is applied to address potential endogeneity issues and to produce robust empirical results. The results reveal that FDI significantly contributes to the reduction of infant and child mortality rates in the region. Additionally, the findings highlight that improved governance, particularly through effective control of corruption, enhances the positive impact of FDI on health outcomes. Good governance is shown to be a critical factor in maximizing the benefits of FDI for improving public health. The study concludes that FDI can be a powerful tool for improving health outcomes in Sub-Saharan Africa, particularly when supported by strong governance structures. The positive interaction between FDI and good governance underscores the importance of policy measures aimed at enhancing institutional quality in the region. The findings suggest that policymakers in Sub-Saharan Africa should focus on strengthening governance frameworks to attract more FDI and maximize its benefits for public health. Future research should explore the long-term effects of governance on the FDI-health relationship and examine sector-specific impacts to identify the most effective channels through which FDI can improve health outcomes.
Keywords: Health Status; Foreign Direct Investment; Governance; GMM Method; Sub-Saharan Africa; Togo